INOVASI 20 RESEP COCKTAIL DARI 10 DESTINASI SUPER PRIORITAS DI INDONESIA SEBAGAI SARANA PROMOSI PARIWISATA - Tarore Rumani, David Hendrick; Hagan Mario Susanto; Kevin Gustian Yulius; Theodosia C. Nathalia (JURNAL ILMIAH EDUNOMIKA, 2025)
This study explores the innovation of cocktail recipes inspired by the distinctive features of Indonesia's 10 Super Priority Destinations. The cookbook blends local spices with cultural narratives, aiming to create unique recipes that embody the identity of each destination while supporting sustainable tourism efforts. These recipes are carefully designed to showcase the richness of Indonesian flavors through rempah (spices) such as ginger, turmeric, and cinnamon, paired with visual elements reflecting each destination’s natural beauty, such as tropical beaches and lush green landscapes. The combination of culinary artistry and cultural storytelling transforms the cookbook into more than just a recipe collection—it becomes a strategic tool for promoting Indonesian tourism and cultural heritage. The research applies an iterative design process, involving audience feedback and testing, to refine the content and ensure it aligns with audience preferences. The visual aesthetics of the cookbook, including layout design, illustrations, and photography, emphasize readability and cultural relevance. The findings highlight the importance of incorporating cultural and natural elements into promotional strategies for local products. By bridging culinary traditions with modern marketing techniques, this study positions the cookbook as an innovative approach to fostering global appreciation for Indonesia’s tourism and cultural diversity